The role of makerspaces in innovation processes: an exploratory study - David Zakoth; Oliver Mauroner; Jutta Emes (R&D Management, 2023)
Makerspaces democratize technology access and therefore improve the chances for innovation and entrepreneurship. Nevertheless, we know little about how innovation happens in collaborative innovation spaces like makerspaces. To unleash the full potential of makerspaces, it is essential to understand what resources and environments support innovation for makerspace users. Against this background, this research study aims to explore how different makerspace user groups leverage makerspace resources during their innovation process. To achieve this, we use the resource-based view in combination with an open innovation perspective and examine the relevance of makerspace resources (knowledge, technology, social, and financial) during the different stages of the innovation journey (ideation, development and prototyping, commercialization and diffusion). In contrast to prior work, we focus on different makerspace user groups within an industry-specific makerspace and investigate how open innovation strategies (inbound, outbound, and coupled) are used to leverage the makerspace resources to develop innovation projects. Since the object of investigation is broadly unexplored and complex, we use an embedded single case study approach to explore 10 different projects within a makerspace with a specific focus on photonics. Photonics is described as a so-called enabling technology that carries a considerable potential for cross-industry innovation. The qualitative content analysis revealed that professional and hobby users differ in their makerspace resource use and their modes of openness across the innovation journey. Furthermore, we find that makerspaces can take the role of a facilitator or incubator depending on who uses the makerspace to innovate.
Keywords: 650